Nancy Drew Chick-napped! The zoo crew - Keene, Carolyn; Pamintuan, Macky (Aladdin Paperbacks New York, NY, 2015)
Chick-napped: When the newly hatched chicks disappear from the classroom, Nancy and her friends have a job on their hands to find out who stole the baby chicks